The long-term (five years) effects of prednisone therapy in children with frequently relapsing nephrotic syndrome: A controlled study of anthropometric parameters and metabolic abnormalities: Growth and metabolic abnormalities in nephrotic children on prednisone therapy - Soliman, Ashraf T; Hamed, Noor; De Sanctis, Vincenzo; Elbaba, Mostafa; Alyafei, Fawzia; Alaaraj, Nada; Ahmad, Shayma; Itani, Maya; Al-Naimi , Fatima; Khater, Doaa (Acta Biomedica Atenei Parmensis, 2022)
Background: Steroids are the main drugs used for the treatment of nephrotic syndrome (NS) in children. Aim of the study: We investigated the steroid effect on linear growth and weight gain as well as the prevalence of different metabolic components and dysglycemia in children with NS with multiple relapses for 5 years in relation to the cumulative dose of steroids. Study population and sample size: Data of 30 children with NS were analyzed retrospectively. They received prednisolone treatment as advised by international guidelines. The cumulative dose of prednisolone (CDP) over the 5 years was calculated for each child. Their growth and different metabolic criteria, including impaired fasting glucose (IFG), high LDL and cholesterol, lower HDL, and high blood pressure studied over this period and compared with the data for 66 age-matched obese non-nephrotic children. Results: The mean CDP was 100 ± 63 mg /kg/yr given over an average duration of 5 years. The height-SDS was not affected after 3 years but decreased by -0.4 SD after 5 years. The body mass index-SDS increased from 0.65 to 0.97 and 1.1 after 3 and 5 years, respectively. Obesity and overweight increased from 25% pre-treatment to 59.2% after 5 years of treatment. After 5 years of treatment, IFG was detected in 35 %, hypertension in 40%, high LDL in 77%, and high cholesterol in 80%. Conclusion: In children with frequently relapsing NS, long-term steroid therapy was associated with a higher rate of obesity, short stature as well as the occurrence of different metabolic syndrome (MetS